Ring Closure Matrix - Randic, Milan; Novic, Marjana; Plavsic, Dejan (Current Organic Chemistry, 2015)
We consider generalization of the terminal matrix of Zaretsky, in which only distances are listed between terminal vertices of acyclic graphs, to a condensed matrix for cyclic and polycyclic systems. Some 50 years ago Zaretsky has proved that the distance matrix between terminal vertices of acyclic graphs allows full reconstruction of the graph. We consider the question: Is there a subset of vertices in cyclic and polycyclic graphs which would allow from information on their distances a full reconstruction of the graph? As we report in this publication a distance matrix confined to a distance between the set of ring closure vertices may offer a positive answer to the considered problem.
Keywords: ring closure matrix